Legal Responsibility Of Medical Personnel In Carrying Out Medical Procedures - Muhammad Nur Aji Basuki; Wardah Yuspin; Siti Soekiswati (IHSA Institute, 2024)
Informed consent is a statement given by a patient to a doctor that he agrees to a medical procedure. Apart from that, informed consent itself is a form of communication between the patient and the doctor with the aim of providing information regarding surgical and/or treatment plans, surgical risks, surgical benefits, disease prognosis and etc. The aim of this study is to analyze the medical responsibility of medical personnel for medical procedures through informed consent. This research uses empirical juridical research. The results of this study explain the important role of informed consent in the practice of medical procedures in hospitals by medical personnel and the responsibility of medical personnels when there are allegations of malpractice committed due to negligence by medical personnel in carrying out their obligations to carry out medical procedures on patients